How self‐esteem and narcissism differentially relate to high and (un)stable feelings of status and inclusion. Issue 6 (18th June 2020) - Benson, Alex J.; Giacomin, Miranda
Abstract: Objective: We tested how self‐esteem and grandiose narcissism are associated with people's level and instability of status and inclusion. Method: In Studies 1 and 2, we used latent profile analysis (Study 1, N  = 989; Study 2, N  = 470, 111 teams) to examine how people felt about their level and instability of status and inclusion. In Study 3, we used daily diary reports ( N  = 287, 1, 286 daily observations) to track people's level and instability of status and inclusion. Results: Higher levels of status and inclusion did not always correspond to more stable beliefs about one's social standing. Self‐esteem predicted higher and more stable feelings of status and inclusion. Although narcissistic admiration also predicted higher levels of status and inclusion, we found mixed evidence regarding its link to the instability of such feelings. Narcissistic rivalry, however, predicted more unstable feelings of status and inclusion. Conclusions: By modeling the heterogeneity of status and inclusion feelings across subgroups (Studies 1 and 2) and documenting the degree of instability people experience regarding such feelings (Study 3), these results provide insight into how self‐esteem and narcissism relate to the level and instability of status and inclusion.